Voices from the past - Mazar, Amihay, 1942-; Trone, Alexandra, 1933-; Cizik, Milka (Irvington-on-Hudson, N.Y. : Harvey House, 1968)
Presents, in chronological order from the earliest period from which there are artifacts, the discoveries of archeologists working in the B iblical land of Palestine and what they have contributed to our knowled ge of history and life in this time and place.
Includes bibliographical references: p. 185-186.
Keywords: Palestine -- Antiquities -- Juvenile literature; Palestine -- Antiquities